2013
DOI: 10.3390/ijms14022410
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Anticancer Effects: Review

Abstract: Melatonin (N-acetyl-5-methoxytryptamine, MLT), the main hormone produced by the pineal gland, not only regulates circadian rhythm, but also has antioxidant, anti-ageing and immunomodulatory properties. MLT plays an important role in blood composition, medullary dynamics, platelet genesis, vessel endothelia, and in platelet aggregation, leukocyte formula regulation and hemoglobin synthesis. Its significant atoxic, apoptotic, oncostatic, angiogenetic, differentiating and antiproliferative properties against all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 128 publications
5
110
0
6
Order By: Relevance
“…Although, the mechanisms underlying are not fully understood, melatonin might exert its ant-cancer role via inducing tumor cells apoptosis and anti-proliferation and anti-angiogenesis (Di Bella et al, 2013). Melatonin has been described to be involved in inhibitory influences on sex hormone levels (Cohen et al, 1978), which have been reported to be associated with cancers of breast, endometrium, ovary, prostate, and thyroid (Henderson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the mechanisms underlying are not fully understood, melatonin might exert its ant-cancer role via inducing tumor cells apoptosis and anti-proliferation and anti-angiogenesis (Di Bella et al, 2013). Melatonin has been described to be involved in inhibitory influences on sex hormone levels (Cohen et al, 1978), which have been reported to be associated with cancers of breast, endometrium, ovary, prostate, and thyroid (Henderson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ramos cells (human Burkitt's lymphoma B cells) are very sensitive to melatonin caused by a dose-dependent G1-phase cell cycle arrest and apoptosis. On the other hand, melatonin in MCF-7 cells induces a delay in the progression of cell cycle, which is largely mediated through the involvement of the TGF-ÎČ pathway (Di Bella et al 2013;SĂĄnchez-Hidalgo et al 2012;Cucina et al 2009). In addition to apoptosis, melatonin can induce other cell death pathways in cancerous cells, including autophagy and senescence (Hong et al 2014).…”
Section: Induction Of Apoptosismentioning
confidence: 99%
“…This hormone exerts oncostatic activity through a variety of mechanisms, including antiproliferative actions, anticancer immunity stimulation, modulation of expression of oncogenes, antiinflammatory, antioxidant, antiangiogenic and antimetastatic effects (20).…”
Section: Introductionmentioning
confidence: 99%